Investigating the Failure Mechanism of Jointed Rock Slopes Based on Discrete Element Method - Chao Peng; Qifeng Guo; Zhenxiong Yan; Minglong Wang; Jiliang Pan (Advances in Civil Engineering)
This paper presents a comprehensive engineering method to investigate the failure mechanism of the jointed rock slopes. The field geology survey is first carried out to obtain the slope joint data. A joint network model considering the structural complexity of rock mass is generated in the PFC software. The synthetic rock mass (SRM) approach for simulating the mechanical behavior of jointed rock mass is employed, in which the flat-jointed bonded-particle model (FJM) and smooth joint contact model (SJM) represent intact rock and joints, respectively. Subsequently, the effect of microparameters on macromechanical properties of rock is investigated for parameter calibration. Moreover, the scale effect is analyzed by multiscale numerical tests, and the representative elementary volume (REV) size in the selected research area is found as 16 m × 16  m × 16 m. The microparameters of the SRM model are calibrated to match the mechanical properties of the engineering rock mass. Finally, an engineering case from Shuichang open-pit mine is analyzed and the failure process of the slope during the excavation process from micro- to macroscale is obtained. It has been found that failure occurs at the bottom of the slope and gradually develops upwards. The overall failure of the slope is dominated by the shallow local tension fracture and wedge failure.